A Garden as a Niche: Botany and Imperial Politics in the Early Nineteenth century Dutch Empire - Weber, Andreas (Studium, 2019)
This essay provides a fresh view on early history of the botanical garden in Buitenzorg by zooming in on the activities of the gardens’ first and second directors: Caspar Georg Carl Reinwardt and Carl Ludwig Blume. In particular under Blume’s aegis the garden was under constant threat which eventually led to the temporary closure of the garden in 1826. The essay conceptualizes the garden as a provisional niche, in which collectors, gardeners, merchants, administrators, and plant experts with diverse socio-economic backgrounds and networks came together to negotiate the relationship between botany and imperial politics. Taken together this essay argues that plant science and the garden’s institutional development need to be analyzed as part of a much wider history of colonial management and agricultural exploitation.